FORMULATION OF SUNSCREEN CREAM OF PARIJOTO FRUIT EXTRACT (Medinilla speciosa Blume) AND IN VITRO SPF VALUE TEST - Elsa Tamara Geraldine; Ema Dwi Hastuti (Sanata Dharma University, 2018)
Sunscreen preparations are cosmetic preparations used as a protection to reduce the impact of sun exposure whose formulations contain active ingredients to absorb or diffuse sunlight, especially in areas of ultraviolet and infrared wave emissions. One of the potential natural ingredients for a sunscreen is parijoto fruit (Medinilla speciosa Blume). It contains flavonoid compounds that are able to prevent the harmful effects of UV rays. The objective of this research is to find out the formula of sunscreen cream of parijoto extract that meets the good physical quality of cream and to find out the result of SPF value test of parijoto fruit extract as sunscreen cream preparation in Vitro. The design of the study was experimental research conducted in the laboratory. The sample used in this research was parijoto made into thick extract by maceration method. Further, the viscous extract obtained was made to be a sunscreen cream and then tested either its physical evaluation or calculation of SPF value. The results of this study indicate that the preparation of sunscreen cream of parijoto fruit extract included in the extra protection category with the value is 6.66 and can be made into the good and stable preparations. The sunscreen cream of parijoto fruit extract has good physical properties and also has activity as UV protection in vitro.